Genetic variation in natural populations of Acacia visco (Fabaceae) belonging to two sub-regions of Argentina using AFLP - Pometti, Carolina Luciana (2016)
Acacia visco is a tree native to South America that grows in central and northwest region of Argentina, north Chile and Bolivia and has also been introduced to Africa and naturalized in Europe. Little is known about genetic diversity and genetic structure of this species. Therefore, we studied natural Argentinean populations of A. visco using the AFLP technique, by determining the genetic diversity of the species and its genetic structure, considering the proportion of the species diversity explained within and between the two sub-regions where populations were this species is present in the country. Fourteen of the 445 loci obtained appeared to be under diversifying selection. The remaining 431 neutral loci showed a mean of 60.89 % of percentage of polymorphic loci. The estimates of genetic diversity HE were generally high. The FST (0.126) was highly significant, providing evidence for genetic structure among populations. Hierarchical AMOVA indicated that variation between sub-regions was 2.1 % and highly significant. The higher component of variance was found within populations (77.4 %). STRUCTURE analysis showed an optimal number of K = 6. This result was consistent with those obtained by UPGMA from Nei’s distances and Canonical Discriminant Analysis. Since differentiation of A. visco populations in sub-regions was highly significant, a suitable management strategy for the use of this species in restoration programs would be focus on sampling seeds of a high number of individual trees within populations and also ensure a comprehensive coverage of the entire ecological amplitude of this species.